Study on incorporation of graphene oxide (GO) in polyvinyl chloride (PVC) mixed matrix membrane (MMM) to enhance CO2/CH4 separation - Raj Krishna Roshan, Kanasan (2020)
Methane, CH4 unique role as a greenhouse gas and as the primary component of natural gas means that reducing CH4 emissions can yield significant economic, environmental and operational benefits. Membranes is a dynamic and rapidly growing in the field of separation of gas. In membrane-based gas separation process, components are separated from their mixtures by differential permeation through membranes. Mixed matrix membranes (MMMs) comprise of a continuous polymer phase and a dispersed filler phase, are pursued by many researchers to achieve higher gas permeability and selectivity. Polyvinyl chloride (PVC) is a flexible and durable polymer with good mechanical and chemical stability, including hard segments, which leads to low polymeric chain segmental motion and low permeability. Graphene oxide (GO) was also employed as an additive in membrane fabrication in order to improve the membrane characteristics. In this study of gas separation using mixed matrix membrane, gases such as CO2 and CH4 are used. The objectives of this research were to synthesize MMMs PVC/GO, to screen and optimize parameters using FFD, and characterize the produced MMMs. The development of MMMs PVC/GO was based on 5 factors, which were the weight ratio of PVC of ratios 20 % and 15 %, weight ratio of GO of ratios 2 % and 4 %, pressure (bar) during single gas permeation of 1 bar or 3 bar, types of solvent used which were N, N-Dimethylformamide (DMF) and N-methyl-2-pyrrolidone (NMP), and time for casted MMMs immersed in coagulation bath (s) at 300 s or 600 s, via dry/wet phase inversion method using DoE of 25 fractional factorial design. Performance study is carried out with produced MMMs with the gas permeation device, using CO2 and CH4 gas. Based on the screening tests, the run which was made up of factors PVC 20 %, GO 4 %, 1 bar of pressure during gas permeation, NMP solvent, and immersion time of 300 s, shows to have the highest selectivity at 26.09 which is above the upper bound lines in the Robeson’s Upper bound plot. Fractional Factorial Design (FFD) was applied to reduce the number of influenced factors during MMMs preparation. Factors removed were the time membrane immersed in water bath (s), and also gas pressure during gas permeation test. Optimization using Central Composite Design (CCD) via Design Expert was carried out and showed an improvement in error margin where the best 3 factors with the highest effect contribution from screening indicated errors less than 5 %, indicating the model of the experimental design can be used for selectivity prediction of any condition in the scope of study. Factors used for optimization runs were the weight ratios (wt.%) of PVC and GO, and type of solvents (DMF or NMP). Optimization tests shows that the run with the highest selectivity at 50.94, with factors of PVC 20 %, GO 4 % and NMP solvent. The produced MMMs are characterized using Scanning Electron Microscope – Energy Dispersive X-ray (SEM – EDX), Fourier Transform Infrared Spectroscopy FTIR, and Atomic Force Microscope (AFM). SEM showed the MMMs had a thickness of 223 µm. EDX showed the presence of elements carbon (C), oxygen (O), and chlorine (Cl), where both elements can be found in PVC and GO, proving its presence. FTIR shows the presence of the functional groups of PVC and GO according to its respective wavelength. AFM shows the root mean square (RMS) to be 97.86 nm which is below 100 nm, where the surface is considered as smooth.